Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1161/circulationaha.110.970038
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Expression and Activity of Extracellular Matrix-Degrading Enzymes in Regions of Low Endothelial Shear Stress Colocalize With Coronary Atheromata With Thin Fibrous Caps in Pigs

Abstract: Background The molecular mechanisms that determine the localized formation of thin-capped atheromata in the coronary arteries remain unknown. This study tested the hypothesis that low endothelial shear stress augments the expression of matrix-degrading proteases and thereby promotes the formation of thin-capped atheromata. Methods and Results Intravascular ultrasound–based, geometrically correct 3-dimensional reconstruction of the coronary arteries of 12 swine was performed in vivo 23 weeks after initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 27 publications
(56 reference statements)
5
129
0
10
Order By: Relevance
“…Thus, it is unknown to what extent high blood pressure contributes to the vulnerable phenotype in the upstream low-flow region compared to the downstream, oscillatory, low-pressure regions. In other models, both low shear and transverse shear were strongly correlated with regions of vulnerability within plaques (77)(78)(79). Plaque rupture itself also depends on wall strain.…”
Section: Plaque Progression and Remodelingmentioning
confidence: 82%
“…Thus, it is unknown to what extent high blood pressure contributes to the vulnerable phenotype in the upstream low-flow region compared to the downstream, oscillatory, low-pressure regions. In other models, both low shear and transverse shear were strongly correlated with regions of vulnerability within plaques (77)(78)(79). Plaque rupture itself also depends on wall strain.…”
Section: Plaque Progression and Remodelingmentioning
confidence: 82%
“…6 -8 Areas of moderate or physiological shear stress are generally vasculoprotective, with increased expression of atheroprotective molecules, such as nitric oxide and decreased expression of degrading enzymes. 8,9 Areas of high ESS may be associated with atrophy of smooth muscle cells, increased macrophages, matrix degradation, increased thrombogenicity, and high mechanical strain. 10 -14 Pilot serial studies of the anatomic natural history of coronary disease in humans using small numbers of patients have confirmed that areas of low ESS are indeed associated with an increase in plaque size over time and associated expansive or constrictive remodeling responses.…”
Section: Article See P 779mentioning
confidence: 99%
“…To characterize the different flow patterns, several hemodynamic parameters have been developed and investigated. These parameters have been shown to strongly correlate with the development of vascular pathology, mainly in the arterial system (17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies applied various methodologies in an effort to set a pathological threshold value for TAWSS (17)(18)30 Compared to non-stented SVGs, the failure rate of stented SVGs was significantly lower than in the left territory but significantly higher in the right territory. As previously described (15), the high failure rate in the right territory was observed when either metallic clips, rather than sutures, were used to ligate side branches (62% versus 20% respectively) or when the stent was fixated to the proximal and/or distal anastomoses although contra-indicated by the protocol (75% versus 33.3% respectively).…”
mentioning
confidence: 99%